At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

If the endpoints of [tex]\(\overline{AB}\)[/tex] are [tex]\(A(-2, 3)\)[/tex] and [tex]\(B(1, 8)\)[/tex], which shows the correct way to determine the coordinates of point [tex]\(C\)[/tex], the midpoint of [tex]\(\overline{AB}\)[/tex]?

A. [tex]\(M = \left( \frac{-2+3}{2}, \frac{1+8}{2} \right)\)[/tex]

B. [tex]\(M = \left( \frac{-2+1}{2}, \frac{3+8}{2} \right)\)[/tex]

C. [tex]\(M = \left( \frac{-2-3}{2}, \frac{1-8}{2} \right)\)[/tex]

D. [tex]\(M = \left( \frac{-2-1}{2}, \frac{3-8}{2} \right)\)[/tex]


Sagot :

To find the midpoint [tex]\( C = (M_x, M_y) \)[/tex] of a line segment [tex]\(\overline{AB}\)[/tex] where the endpoints are [tex]\( A(-2, 3) \)[/tex] and [tex]\( B(1, 8) \)[/tex], we use the midpoint formula. The formula for finding the midpoint [tex]\( M \)[/tex] of a line segment with endpoints [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is given by:

[tex]\[ M = \left( \frac{x_1 + x_2}{2}, \frac{y_1 + y_2}{2} \right) \][/tex]

Given the coordinates of [tex]\(A\)[/tex] are [tex]\((A_x, A_y) = (-2, 3)\)[/tex] and of [tex]\(B\)[/tex] are [tex]\((B_x, B_y) = (1, 8)\)[/tex], we substitute these values into the midpoint formula:

For the x-coordinate of the midpoint [tex]\(M_x\)[/tex]:

[tex]\[ M_x = \frac{A_x + B_x}{2} = \frac{-2 + 1}{2} = \frac{-1}{2} = -0.5 \][/tex]

For the y-coordinate of the midpoint [tex]\(M_y\)[/tex]:

[tex]\[ M_y = \frac{A_y + B_y}{2} = \frac{3 + 8}{2} = \frac{11}{2} = 5.5 \][/tex]

Therefore, the coordinates of the midpoint [tex]\(C\)[/tex] are:

[tex]\[ M = (-0.5, 5.5) \][/tex]

Reviewing the given choices:

1. [tex]\(M = \left( \frac{-2 + 3}{2}, \frac{1 + 8}{2} \right)\)[/tex]
2. [tex]\(M = \left( \frac{-2 + 1}{2}, \frac{3 + 8}{2} \right)\)[/tex]
3. [tex]\(M = \left( \frac{-2 - 3}{2}, \frac{1 - 8}{2} \right)\)[/tex]
4. [tex]\(M = \left( \frac{-2 - 1}{2}, \frac{3 - 8}{2} \right)\)[/tex]

The correct formula and corresponding choice is:

[tex]\[ M = \left( \frac{-2 + 1}{2}, \frac{3 + 8}{2} \right) \][/tex]

Thus, the correct answer is:

[tex]\[ M = \left( \frac{-2 + 1}{2}, \frac{3 + 8}{2} \right) \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.